The essence of the concept «productive and creative competence of the future engineer-teacher - Masych, V. (Problems of Engineer-Pedagogical Education, 2018)
Productive and creative competence is an integrative personal and professional characteristic of the future engineer-teacher, which ensures its commitment to the successful implementation of professional activity by implementing the creative potential of both – their own and those who are learning. The process of forming a productive and creative competence of the future engineer-teacher can be defined as the systematic accumulation of positive content in its quantitative and qualitative changes that allow carrying out productive creative professional and educational activities. Considering the formation of a productive and creative competence in higher vocational education system, we can talk about the readiness of the graduate to the professional and educational activities, its ability to apply knowledge, skills and experience for successful professional fulfillment, efficiently using your own creativity. The future engineer-teacher with the generated productive and creative competence is a subject which has some of its components, it is allowed to carry out the vocational and educational activities productively, creatively and at the highest level.